Chemical reactions inside single-walled carbon nano test-tubes. - Britz, D; Khlobystov, A; Porfyrakis, K; Ardavan, A; Briggs, G (2005)
We report the application of SWNTs as templates for forming covalent polymeric chains from C(60)O reacting inside SWNTs; the resulting peapod polymer topology is different from the bulk polymer in that it is linear and unbranched.